2022
DOI: 10.1186/s12872-022-02481-4
|View full text |Cite
|
Sign up to set email alerts
|

Construction of genetic classification model for coronary atherosclerosis heart disease using three machine learning methods

Abstract: Background Although the diagnostic method for coronary atherosclerosis heart disease (CAD) is constantly innovated, CAD in the early stage is still missed diagnosis for the absence of any symptoms. The gene expression levels varied during disease development; therefore, a classifier based on gene expression might contribute to CAD diagnosis. This study aimed to construct genetic classification models for CAD using gene expression data, which may provide new insight into the understanding of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Genes such as HLA-DMB 39 , HLA-B 40 , and GPX1 41 were found to be profoundly expressed in cardiomyopathy. While other biomarkers such as RN7SL2 42 , LILRA2 43 , GAS5 44 , TWF2 45 , EGLN2 46 , SNHG6 47 49 , and BRK1 50 have all been previously associated with phenotypic variations linked to CVD, there is limited literature associating protein-coding genes such as RPS28P7 and CTA-363E6.6 to other known CVDs. No direct links were recorded between RN7SL593P and AP003419.11 and known CVDs as well as other non-CVD-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as HLA-DMB 39 , HLA-B 40 , and GPX1 41 were found to be profoundly expressed in cardiomyopathy. While other biomarkers such as RN7SL2 42 , LILRA2 43 , GAS5 44 , TWF2 45 , EGLN2 46 , SNHG6 47 49 , and BRK1 50 have all been previously associated with phenotypic variations linked to CVD, there is limited literature associating protein-coding genes such as RPS28P7 and CTA-363E6.6 to other known CVDs. No direct links were recorded between RN7SL593P and AP003419.11 and known CVDs as well as other non-CVD-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, nevertheless, our research revealed that BCL6 gene expression was up-regulated, which may be connected to negative feedback regulation in individuals with high levels of atherosclerosis. Interestingly, prior research had also discovered increased BCL6 gene expression in individuals suffering from coronary heart disease 40 . Hence, additional mechanisms must be proven through additional tests.…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as HLA-DMB [28], HLA-B [29], and GPX1 [30] were found to be profoundly expressed in cardiomyopathy. While other biomarkers such as RN7SL2 [31], LILRA2 [32], GAS5 [33], TWF2 [34], EGLN2 [35], SNHG6 [36, 37, 38], and BRK1 [39] have all been previously associated with phenotypic variations linked to CVD, there is limited literature associating protein-coding genes such as RPS28P7 and CTA-363E6.6 to other known CVDs. No direct links were recorded between RN7SL593P and AP003419.11 and known CVDs as well as other non-CVD-related diseases.…”
Section: Discussionmentioning
confidence: 99%